2003
DOI: 10.1002/ijc.11295
|View full text |Cite
|
Sign up to set email alerts
|

Detection of micrometastatic breast cancer by means of real time quantitative RT‐PCR and immunostaining in perioperative blood samples and sentinel nodes

Abstract: The aim of our study was to detect micrometastatic breast cancer by epithelial glycoprotein-2 (EGP-2) and cytokeratin 19 (CK19), using immunostaining and real time quantitative reverse transcriptase-polymerase chain reaction (qRT-PCR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 47 publications
1
22
1
Order By: Relevance
“…Our findings are in contrast to the recent results published by Schroder et al (2003) who found that in SNs immunostaining appears to be more sensitive/specific than quantitative PCR for breast tumour cell detection. The apparent discrepancy between our results and that of Schroder et al are likely due to the increased sensitivity achieved by the use of a multimarker panel in combination with the QDA score.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings are in contrast to the recent results published by Schroder et al (2003) who found that in SNs immunostaining appears to be more sensitive/specific than quantitative PCR for breast tumour cell detection. The apparent discrepancy between our results and that of Schroder et al are likely due to the increased sensitivity achieved by the use of a multimarker panel in combination with the QDA score.…”
Section: Discussioncontrasting
confidence: 99%
“…TACSTD1, also known as EPCAM, EGP-2, KS1/4, GA-733-2, and MIC-18, is a human cell surface antigen that is defined by the monoclonal antibody AUAI. TACSTD1 is also the antigen for the antibody Ber-Ep4 and as such has been used in studies to detect lymph node micrometastases in a variety of tumor types, including SCCHN (41,49,50). A recent study has also shown that TACSTD1 is a good marker for RT-PCR-based identification of lymph node micrometastasis in non-small cell lung cancer (9).…”
Section: Discussionmentioning
confidence: 99%
“…CK19 is one of the keratins targeted by the AE1/AE3 antibody cocktail and, as such, is frequently used by pathologists for immunohistochemical detection or confirmation of lymph node metastases in many cancer types. CK19 has also been used in many RT-PCR-based studies to detect occult lymph node disease in breast cancer (21,24,25). Unfortunately, this gene has at least two pseudogenes that make it difficult to develop a cDNA-specific assay.…”
Section: Discussionmentioning
confidence: 99%
“…TACSTD1 is also known as EPCAM, EGP-2, KS1/4, GA-733-2, and MIC-18 and encodes a cell surface antigen that is defined by the monoclonal antibody AUAI. TACSTD1 is also the antigen for the antibody Ber-Ep4 and as such has been used in several studies to detect lymph node micrometastases in a variety of tumor types, including NSCLC (8,25,26). The recent studies by Wallace et al (22) and Mitas et al (23) also found TACSTD1 (KS1/4 in their article) to be a good RT-PCR-based marker for identification of lymph node metastasis in mediastinal lymph nodes from NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%